2008
DOI: 10.1080/09687680802203380
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol content drives distinct pharmacological behaviours of µ-opioid receptor in different microdomains of the CHO plasma membrane

Abstract: Cholesterol in the plasma membrane of eukaryotic cells contributes to modulating the functions and signalling pathways of numerous transmembrane proteins, including G protein Coupled Receptors (GPCRs). We have previously shown that the function of the human micro-opioid receptor (hMOR) expressed in Saccharomyces cerevisiae is modulated by sterols including cholesterol. Here, we investigated the effects of cholesterol content on hMOR pharmacology and on hMOR partitioning in cholesterol-poor and -rich domains in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
4
17
0
1
Order By: Relevance
“…The results from the sucrose gradient membrane separation experiments are consistent with reports of the localization of -opioid receptors in caveolin-enriched membrane fractions as well as caveolin-poor fractions (9,23). In contrast, we found ␦-opioid receptors only in the same cellular fractions as transferrin receptor, a non-raft marker.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results from the sucrose gradient membrane separation experiments are consistent with reports of the localization of -opioid receptors in caveolin-enriched membrane fractions as well as caveolin-poor fractions (9,23). In contrast, we found ␦-opioid receptors only in the same cellular fractions as transferrin receptor, a non-raft marker.…”
Section: Discussionsupporting
confidence: 82%
“…The receptor, however, is less tightly coupled to G proteins (47) and may depend on cholesterol to aid in this coupling even in non-raft regions of the plasma membrane. This is supported by evidence that cholesterol alone can stabilize receptors in a high affinity state (23), and increasing membrane viscosity with a cholesterol analog has been shown to improve the potency of the -opioid receptor agonist DAMGO to stimulate [ 35 S]GTP␥S binding (22). The heterogeneous distribution of -opioid receptors in caveolin-enriched and caveolin-poor fractions may explain the rather small effect of cholesterol depletion on acute -opioid signaling (either [ 35 S]GTP␥S binding or adenylyl cyclase inhibition).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Reports on the localization of agonist-bound MORs vary. In one study, morphine-bound receptors remained within the rafts but etorphine-bound receptors diffused out of raft domain (Zheng et al, 2008a), but another study found that DAMGO-bound MORs moved into rafts (Gaibelet et al, 2008). The lipid environment can have substantial effects on agonist binding (Lazar and Medzihradsky, 1992) and MOR activity.…”
Section: E Microdomains and Compartmentalizationmentioning
confidence: 99%
“…Crystallization of the four OPrs also required the presence of cholesterol Manglik et al, 2012;Thompson et al, 2012;Wu et al, 2012), although the role of cholesterol as a factor determining the observed structures of these receptors is not discussed by the authors. It has long been known that modulating the cholesterol content of OPr-expressing cell membranes can alter the binding and signal transduction properties of the receptors (Lazar and Medzihradsky, 1992;Xu et al, 2006;Gaibelet et al, 2008;Zheng et al, 2012), although the authors differ in their proposed (non-mutually exclusive) mechanisms (e.g., altered membrane microviscosity, receptor partition into lipid rafts, facilitation of association with G proteins, facilitation of dimer formation, modulation of receptor palmitoylation).…”
Section: Receptor Oligomerizationmentioning
confidence: 99%